PERANAN HOTEL LOMBOK RAYA TERHADAP MASYARAKAT SEKITAR DAN DAYA DUKUNGNYA TERHADAP KEBUTUHAN SEKTOR PARIWISATA DI PULAU LOMBOK - Surahman Hidayat (Sekolah Tinggi Ilmu Ekonomi AMM, 2017)
Business Development Hospitality or better known as the hospitality is growing and developing city of Mataram today, this growth trend is certainly an impact on economic growth, especially for stretching around the affected masyarakarat directly from destination tourism sector development is a mainstay of NTB's in an effort to improve Budgets. This study was conducted to see to what extent the role of hotels in absorbing and empower local communities that the spirit of development, as well as the extent of government involvement through BPMP2T institutions as partners businessmen, and representatives of the community. The results of this study can be concluded that the efforts of the ideals of this development has not optimally met along with various constraints that followed, while hotel’s role to support the local government’s program to enhance MICE tourism (Meeting, Insentif, Conference, Eksibition) at this time has collide with central government policy, whereas the domino effect which resulted from this kind of tourism is large enough not only for hotels ennterpreneur which has have decreasing worker, but also has decending in service sector and small-medium bussiness